Modelling of palm oil export trend in Malaysia - Abas, Norzaida; Kamisan, Asrad; Abdul Halim, Syafrina (New Academia Press, 2017)
Oil palm is one of the important export crops of Malaysia. In addition, oil palm industry contributes significantly to the country’s wellbeing by being one of the main contributors to the Gross National Product and provides employments. In this study, time series technique is used to analyse and forecast palm oil exports of Malaysia. While various studies are available on modelling of palm oil, very few studies are found focusing on the modelling of palm oil exports. Model based on multiplicative decomposition method is employed to analyse the monthly exports. Time series data from January 2012 to April 2017 are transformed through a series of procedures to decompose the data into seasonal and trend components. Subsequently, the constructed model is used to make forecasting of future export for several months. Results show that the model is able to replicate the pattern of the observed data. A slight negative trend is detected for the export values. The overall forecasted export values show there is some small fluctuation between the months.